2001
DOI: 10.1021/jf001390b
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oil Solubilization in Oil/Water Food Grade Microemulsions in the Presence of Polyols and Ethanol

Abstract: Microemulsions based on five-component mixtures for food applications and improved oil solubilization have been studied. The compositions included water, oil phase [such as R(+)-limonene and medium-chain triglycerides (MCT)], short-chain alcohols (such as ethanol), polyols (propylene glycol and glycerol), and several surfactants and their corresponding mixtures (nonionic, such as ethoxylated sorbitan esters, polyglycerol esters, sugar ester, and anionic, such as phosphatidylcholine). The phase behavior of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
185
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 32 publications
14
185
0
2
Order By: Relevance
“…Fortunately, early investigators revealed that preparation of microemulsions using solubilization enhancers can lead to the formation of fully dilutable formula at low surfactant/ oil ratio 37 . Considering this concept in the current study, the authors formulated three other non-ionic carvacrol microemulsions containing the common solubilization enhancers namely PG, ethanol and isopropanol as shown in Table 1 systems 3-5 .…”
Section: Results and Discusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fortunately, early investigators revealed that preparation of microemulsions using solubilization enhancers can lead to the formation of fully dilutable formula at low surfactant/ oil ratio 37 . Considering this concept in the current study, the authors formulated three other non-ionic carvacrol microemulsions containing the common solubilization enhancers namely PG, ethanol and isopropanol as shown in Table 1 systems 3-5 .…”
Section: Results and Discusionmentioning
confidence: 99%
“…In more details, PG which is a diol -bearing molecule, can arrange itself at the carvacrol-water interfacial film along with the original surfactant leading to increase of its elasticity and decrease of the interfacial tension. That behavior can lead to enhancement of the spontaneous film curvature, making its value less than zero which in turn prevents formation of gel phases and facilitates formation of microemulsion 37,40 . The dilutable nature of carvacrol microemulsion formulated with water/PG typically fulfilled the aim of this study for selection to the antimicrobial evaluation.…”
Section: Results and Discusionmentioning
confidence: 99%
See 3 more Smart Citations